2010
DOI: 10.1111/j.1741-4520.2010.00279.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary exposure to low doses of bisphenol A: Effects on reproduction and development in two generations of C57BL/6J mice

Abstract: The present study was conducted to examine the effects of low-dose exposure to bisphenol A on reproduction and development in two generations of mice. Pregnant female C57BL/6J mice (F0) were fed a diet containing low doses of bisphenol A (0, 0.33, 3.3, or 33 ppm) from gestational day 6 through postnatal day 22, and the weanlings (F1 and F2) from each F0 and F1 dam group, respectively, were also fed these same concentrations of bisphenol A ad libitum until sacrifice. There were no treatment-related changes in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 43 publications
3
22
0
Order By: Relevance
“…As shown in Supplemental Material, Table S5, several studies have reported that low-dose BPA did not alter gestation length in gestationally plus neonatally exposed mice (Cabaton et al 2011; Kobayashi et al 2010), adult-exposed mice (Tyl et al 2008), or gestationally plus neonatally exposed SD rats (Kobayashi et al 2012). Cabaton et al (2011) reported that low-dose BPA decreased the number of pregnancies and successful deliveries in gestationally exposed mice.…”
Section: Pregnancy Outcomesmentioning
confidence: 99%
“…As shown in Supplemental Material, Table S5, several studies have reported that low-dose BPA did not alter gestation length in gestationally plus neonatally exposed mice (Cabaton et al 2011; Kobayashi et al 2010), adult-exposed mice (Tyl et al 2008), or gestationally plus neonatally exposed SD rats (Kobayashi et al 2012). Cabaton et al (2011) reported that low-dose BPA decreased the number of pregnancies and successful deliveries in gestationally exposed mice.…”
Section: Pregnancy Outcomesmentioning
confidence: 99%
“…Extensive toxicology studies have established no-observedadverse-effect-levels (NOAELs) ranging from 5 to 50 mg/kg/day, further reinforcing the significance of first pass metabolism for mitigating BPA's potential risk (Ema et al, 2001;Tyl et al, 2002Tyl et al, , 2008Howdeshell et al, 2008;Ryan et al, 2010;Kobayashi et al, 2010Kobayashi et al, , 2012Stump et al, 2010). Delclos et al (2014) and Churchwell et al (2014) reported reproductive effects in rat pups after gavage dosing of dams from gestational day 6 and subsequent gavage dosing of pups from PND1 with 100 and 300 mg/kg/day BPA but not with dosages of 2.7 mg/kg/day or lower.…”
Section: Introductionmentioning
confidence: 98%
“…However, these results may not be reliable, as estrus cycling is not yet consistent in mice at this age, and given the small number of individual mice studied (n=5 per group). This study, and three others [6971], examine effects of BPA on uterine weights. Unfortunately, none of these studies [61,6771] reported measures to control for effects of the estrus cycle on uterine weights, i.e.…”
Section: Resultsmentioning
confidence: 99%